The Effect Of Application Of Film Learning Strategies On The Motivation Of Learning Student’s Class IV UPT SPF SD Negeri Sudirman III Kecamatan Ujung Pandang Kota Makassar - Hamzah Pagarra; Khaerunnisa Khaerunnisa; Sitti Nur Annisa Muharyati (International Journal of Elementary School Teacher, 2022)
The purpose of this study are (1) To describe the application of movie learning strategies to learning class IV UPT SPF SD Negeri III Sudirman Kecamatan Ujung Pandang Kota Makassar. (2) To describe the picture of learning motivation in student’s class IV UPT SPF SD Negeri III Sudirman Kecamatan Ujung Pandang Kota Makassar. (3) To find out whether there is an influence of the application of movie learning strategies on student learning motivation class IV UPT SPF SD Negeri III Sudirman Kecamatan Ujung Pandang Kota Makassar. The method is  experimental research using quasi-experimental design and quantative approaches.  The population in this study was all class IV UPT SPF SD Negeri III Sudirman Kecamatan Ujung Pandang Kota Makassar with a total of 53 students, while the sample was students of the IVA class as an experimental class with 27 students and class IVB as a control class with 26 students. The research data was obtained by providing a learning motivation questionnaire in the form of pre-test and post-test as well as an observation sheet for the implementation of movie learning strategies. Data analysis techniques are descriptive analysis and inferential statistical analysis with the help of the IMB SPSS statistics version program. Thus, it can be concluded that the application of movie learning strategies can increase student learning motivation class students IV UPT SPF SD Negeri Sudirman III Kecamatan Ujung Pandang Kota Makassar.